Ethical Issues in Engineering Seminar - Anonymous (Online Ethics Center, 2006)
"The description and syllabus of a class on ethical issues in engineering."
Instructor Materials
Keywords: Ethical Decision-Making; Workplace Ethics; Safety; Whistleblowing; Social Responsibility